Gambaran Kualitas Tidur Mahasiswa Terhadap Intensitas Menonton Drama Korea Fakultas Ilmu Kesehatan Universitas Bina Bangsa - Hernawati; Ningsih, Rastia; Esmayanti, Ratna; Kurnia, Nia Marlina; Fiana, Marista (Public Health and Safety International Journal, 2025)
Sleep quality is an important factor in maintaining physical and mental health. The Korean Wave phenomenon is an activity of watching Korean dramas that increases the curiosity of the audience to always want to watch the continuation of the story in each episode or often called chasing broadcasts so that it can cause a person's sleep quality to be poor. The purpose of this study was to determine the picture of the quality of sleep of students regarding the intensity of watching Korean dramas at the Faculty of Health Sciences, Bina Bangsa University. This research method uses a quantitative descriptive method, with a population of 77 people. The sampling technique used cross-sectional with the distribution of the Sleep Quality Index Questionnaire (PSQI) in the form of Google Form and distributed via Whatsapp. The results showed that the majority of students at the Faculty of Health Sciences, Bina Bangsa University had poor sleep quality, as many as 47 respondents (61.0%), while from the results of this number there were 45 respondents (58.4%) who had a high intensity of watching Korean dramas (watching ≥3 hours per title). The conclusion of this study shows that some of the descriptions of the quality of sleep of FIKes UNIBA students regarding the intensity of watching Korean dramas are poor.